Union of the Comoros : 2006 Article IV Consultation and Fourth Staff Review and Extension of the Staff-Monitored Program; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Union of the Comoros. (IMF Staff Country Reports; Country Report, 2006)
Comoros faces significant economic and political challenges. The fiscal priorities are to restore revenues and curtail spending so that domestic arrears can be reduced and the program brought back on track. Clearing external arrears is a key hurdle to debt sustainability. Improvements to the investment climate are critical for attracting foreign direct investment. Financial sector development is needed to support private sector growth and economic diversification. If implemented successfully, the government's policies could be the basis for a Poverty Reduction and Growth Facility arrangement.